2007
DOI: 10.1182/blood-2006-10-050054
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose imatinib mesylate leads to rapid induction of major molecular responses and achievement of complete molecular remission in FIP1L1-PDGFRA–positive chronic eosinophilic leukemia

Abstract: The FIP1L1-PDGFRA fusion gene is a recurrent molecular lesion in eosinophiliaassociated myeloproliferative disorders, predicting a favorable response to imatinib mesylate. To investigate its prevalence, 376 patients with persistent unexplained hypereosinophilia were screened by the United Kingdom reference laboratory, revealing 40 positive cases (11%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
190
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(208 citation statements)
references
References 25 publications
(48 reference statements)
9
190
0
9
Order By: Relevance
“…57,58 The response to imatinib is typically within days to a few weeks, and complete hematologic and molecular remission is almost universal. 7,[58][59][60][61][62] Whereas maintenance of remission has been reported with imatinib doses as low as 100 mg weekly, 63 daily dosing seems more prudent due to the theoretical risk of inducing resistance. Although early studies demonstrated relapse in all PDGFRA-positive patients within 2 to 3 months of imatinib discontinuation, 64 recent data suggests that cure may be possible in some cases, especially after prolonged molecular remission.…”
Section: Pdgfr-associated Mpnmentioning
confidence: 99%
“…57,58 The response to imatinib is typically within days to a few weeks, and complete hematologic and molecular remission is almost universal. 7,[58][59][60][61][62] Whereas maintenance of remission has been reported with imatinib doses as low as 100 mg weekly, 63 daily dosing seems more prudent due to the theoretical risk of inducing resistance. Although early studies demonstrated relapse in all PDGFRA-positive patients within 2 to 3 months of imatinib discontinuation, 64 recent data suggests that cure may be possible in some cases, especially after prolonged molecular remission.…”
Section: Pdgfr-associated Mpnmentioning
confidence: 99%
“…Similarly, the fusion was found in only 40 of 376 individuals (11%) in a European trial of patients with persistent, unexplained hypereosinophilia. 10 In a Mayo series, 11 of 89 patients (12%) with moderateto-severe eosinophilia were FIP1L1-PDGFRA positive. 11 In a follow-up series of 714 unselected patients with eosinophilia, only 3% were fusion positive.…”
Section: Terminology and Classificationmentioning
confidence: 99%
“…Asimismo, en otra serie de 40 pacientes, se reportó remisión hematológica por más de un año, aún en aquéllos tratados con 100 mg/día de imatinib. Esto traduce una mayor sensibilidad general que LMC al tratamiento con ITK de primera línea 9,13 . En relación a la duración del tratamiento, se recomienda que éste sea permanente y en la dosis a la cual se haya producido respuesta.…”
Section: Discussionunclassified